2017
DOI: 10.1093/bjc/azx008
|View full text |Cite
|
Sign up to set email alerts
|

Intoxication and Assault: An Analysis of Crown Court Sentencing Practices in England and Wales

Abstract: This is a repository copy of Intoxication and assault: an analysis of Crown Court sentencing practices in England and Wales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…In so doing, the Council would be promoting the principle of consistency of approach that sentencers are expected to uphold; only in this case the principle would be applied to the Council's own design of sentencing guidelines. We would also like to encourage other researchers to use our scale of severity, which could be applied to a wide range of areas, such as recent research on the effect of aggravating and mitigating factors (Maslen 2015;Lightowlers and Pina-Sánchez 2017;Belton 2018), consistency in sentencing (Pina-Sánchez and Linacre 2013; Pina-Sánchez and Grech 2017; Reid and MacAlister 2018), discrimination (Brandon and O'Connell 2018;Lammy 2017), proportionality (Fleetwood et al 2015;Vibla 2015), or deterrence, recidivism and risk assessment (Bell et al 2014;Raaijmakers et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In so doing, the Council would be promoting the principle of consistency of approach that sentencers are expected to uphold; only in this case the principle would be applied to the Council's own design of sentencing guidelines. We would also like to encourage other researchers to use our scale of severity, which could be applied to a wide range of areas, such as recent research on the effect of aggravating and mitigating factors (Maslen 2015;Lightowlers and Pina-Sánchez 2017;Belton 2018), consistency in sentencing (Pina-Sánchez and Linacre 2013; Pina-Sánchez and Grech 2017; Reid and MacAlister 2018), discrimination (Brandon and O'Connell 2018;Lammy 2017), proportionality (Fleetwood et al 2015;Vibla 2015), or deterrence, recidivism and risk assessment (Bell et al 2014;Raaijmakers et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the timing or the location of the offence are applied to account for very diverse settings without clear guidance about which locations might represent an aggravating factor. And there is considerable debate over the extent that being under the influence of drugs or alcohol should be used as an aggravating factor (Dingwall, 2006; Lightowlers and Pina-Sánchez, 2017; Padfield, 2011). Second, the treatment of previous convictions as a Step Two factor in spite of its vast importance in deciding sentence severity (Roberts and Pina-Sánchez, 2014) seems to be something against which judges are rebelling.…”
Section: Discussionmentioning
confidence: 99%
“…At the outset, we drew attention to the new wave of studies that resulted from the publication of the CCSS, transforming sentencing research in England and Wales into a more empirically based discipline. These recent contributions have shed new light on important topics such as proportionality (Fleetwood et al, 2015); consistency (Pina-Sánchez, 2015; Pina-Sanchez and Grech, 2018; Pina-Sánchez and Linacre, 2013, 2014), individualization (Roberts et al, 2018), severity (Pina-Sánchez et al, 2016), compliance with the guidelines (Roberts, 2013a; Roberts and Bradford, 2015) or the use of different case characteristics (Belton, 2018; Irwin-Rogers and Perry, 2015; Lightowlers and Pina-Sánchez, 2017; Maslen, 2015; Maslen and Roberts, 2013; Roberts and Pina-Sánchez, 2014). Added to this, we have demonstrated that unique features of the CCSS can also be exploited to estimate accurately: (1) the specific contribution of each case characteristic on the sentence outcome, something that was previously considered impossible by many sentencing scholars, and the CCSS founders at the Sentencing Council for England and Wales; 10 (2) the degree of unwarranted disparities at different stages of the sentencing process – for the case of Step One decisions those disparities were estimated after controlling for all relevant case characteristics; and (3) the undue influence that different case characteristics might have across the sequence of steps configured in the guidelines, which opens a new and more insightful approach to the study of compliance with the guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies have also found that, as the England and Wales guidelines require, sentencers generally give more weight to ‘Step One’ factors (i.e. those indicating seriousness) than to the additional aggravating and mitigating factors provided in ‘Step Two’ (Fleetwood et al, 2015; Irwin-Rogers and Perry, 2015; Lightowlers and Pina-Sánchez, 2017; Maslen, 2015; Pina-Sánchez and Grech, 2018). More recently, Pina-Sánchez et al (under review) found evidence that judges generally follow the step-sequence in the order prescribed within the guidelines.…”
Section: Sentencing Guidelines As Choice Architecturementioning
confidence: 99%